Improving Teaching Quality Assessment in Smart Classrooms for English Majors: An Integrated Double-Valued Neutrosophic Decision-Making Model - Lu Luo; Cong Wang (Neutrosophic Sets and Systems)
The evaluation of multimedia-based college English teaching aims to assess the impact of multimedia technology on teaching quality and student learning outcomes. With the introduction of multimedia, classroom interactivity is enhanced, and students' interest and engagement are increased. Additionally, multimedia provides more opportunities for self-directed learning, helping students reinforce knowledge outside the classroom. However, the evaluation must focus on the alignment of technology with teaching objectives and whether the use of multimedia truly improves students' language skills and classroom efficiency. The evaluation of smart classroom teaching quality for English majors in universities is a multi-attribute decision-making (MADM) problem. Recently, methods such as the TOPSIS approach have been applied to tackle these challenges. Double-Valued Neutrosophic Sets (DVNSs) are used to represent fuzzy data in the evaluation process. In this study, a Double-Valued Neutrosophic Number TOPSIS (DVNN-TOPSIS) approach is proposed to address MADM problems involving DVNSs. Finally, a numerical case study on the quality evaluation of smart classroom teaching for English majors is provided to demonstrate the effectiveness of the DVNN-TOPSIS approach.